Intra- and Interindividual Variability of Hemostatic Factors and Traditional Cardiovascular Risk Factors in a Three-year Follow-up - Salomaa, Veikko; Rasi, Vesa; Stengård, Jari; Vahtera, Elina; Pekkanen, Juha; Vartiainen, Erkki; Ehnholm, Christian; Puska, Pekka (Thrombosis and Haemostasis, 1998)
Elucidation of the key role of thrombosis in cardiovascular disease events has arisen considerable interest in hemostatic factors and in the repeatability of their determinations. Data on long-term repeatability has, however, remained scanty. We examined twice 208 men and 265 women in North Karelia, eastern Finland. The baseline examination was a part of the FINRISK 1992 Hemostasis Study and the age-range of participants was between 45-64 years. The re-examination took place three years later in 1995. Both surveys followed the same protocol and were carried out during the same season. Spearman rank correlation coefficients between 1992 and 1995 measurements of fibrinogen, factor VII coagulant activity (FVII:C), factor VII antigen (FVII:Ag), and plasminogen were among men 0.72, 0.77, 0.46 and 0.56, respectively. For total cholesterol, HDL-cholesterol, triglycerides and diastolic blood pressure the corresponding coefficients were 0.74, 0.83, 0.66, and 0.54. In women, the coefficient of fibrinogen was lower than in men, 0.62, otherwise the results were similar. Of men belonging to the highest quarter of fibrinogen, FVII:C, FVII:Ag and plasminogen in 1992, 65%, 60%, 53% and 60% belonged to the highest quarter of respective distributions also in 1995. In women, the corresponding proportions were 64%, 65%, 46% and 58%. The modest repeatability of FVII:Ag and plasminogen was mainly due to the high intraindividual variability. However, in comparisons of plasma levels between two groups, relatively small sample sizes seemed to give adequate statistical power to detect possible differences in FVII:Ag and plasminogen. In conclusion, the long-term repeatability of fibrinogen and FVII:C is similar to that of triglycerides and even better than that of diastolic blood pressure, but somewhat lower than the repeatability of total cholesterol. FVII:Ag and plasminogen did not have very good repeatability and more than one measurement of them should be considered if they are used as predictors of cardiovascular disease in prospective studies.